The Effectiveness of Innovation-based Multisectoral Collaboration in Accelerating Stunting Reduction in Indonesia: The Strategic Role of Local Governments - Hamka, Amarun Agung; Ibrahim, Muh. Akmal (KnE Social Sciences, 2025)
Child stunting is a chronic nutritional issue with serious implications for human resource quality. Indonesia has set an ambitious target to reduce the prevalence of stunting among children under 5 to 14% by 2024 through an Accelerated Stunting Reduction Program involving multiple sectors. This literature review analyzes the effectiveness of innovation-based multisectoral collaboration in accelerating stunting reduction in Indonesia, highlighting the strategic role of local governments. Data from the last decade (2015–2025) demonstrate a significant downward trend in stunting prevalence, decreasing from approximately 37% (2013) to 21.6% (2022). This success has been supported by cross-sector collaboration encompassing both specific interventions (health and nutrition) and sensitive interventions (clean water, sanitation, education, and social protection). Program innovations such as the establishment of family assistance teams (Tim Pendamping Keluarga), integrated data dashboard utilization, the healthy kitchen program to overcome stunting (DASHAT), daycare initiatives, and foster parent movements underline the crucial role of local governments in coordinating stakeholders. This study finds that an integrated multisectoral approach, strengthened by local innovations and political commitment, effectively accelerates stunting reduction. Local governments play a strategic role as collaboration initiators, convergence program planners, and intervention implementers at the grassroots level. In conclusion, sustainable, innovation-driven multisectoral collaboration, actively involving local governments, the private sector, academia, civil society organizations, and communities are essential for further accelerating stunting reduction in Indonesia.